Methicillin-Resistant Staphylococcus aureus (MRSA) in Slaughter Houses and Meat Shops in Capital Territory of Pakistan During 2018–2019 - Sadiq, Asma; Samad, Maroof; Saddam,; Basharat, Nosheen; Ali, Shahid; Roohullah,; Saad, Zubaida; Khan, Allah Nawaz; Ahmad, Yasin; Khan, Alam; Khan, Jadoon (Frontiers in Microbiology, 2020)
Livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) is a major concern in many parts of the world, including Pakistan. The aim of this study was to investigate the prevalence of MRSA in slaughterhouses and meat shops in Rawalpindi-Islamabad, Pakistan, 2018-2019. A total of 300 samples were collected: 40 from each of working area, tools (knives, hooks), butcher hands and beef, 30 from each of chicken and mutton, 20 from each of nasal and rectal swabs. S. aureus was phenotypically identified by performing gram staining and biochemical tests. 150 of the 300 samples were confirmed to be S. aureus by phenotypic identification. MRSA was identified among S. aureus positive isolates by performing disk diffusion test and by detecting S. aureus-specific genes such as 16s rRNA, nuc, mecA, spa and coa. Out of 150 isolates 96 (63%) showed resistance to antibiotic cefoxitin, known as a potential marker for detecting MRSA. While all 150 isolates have shown complete resistance to the four antibiotics neomycin, methicillin, ciprofloxacin and tetracycline. The nuc and 16s rRNA genes were detected in all 150 S. aureus-positive isolates and 118 (79%) were confirmed to be MRSA through the detection of the mecA gene. MRSA prevalence was highest in chicken (23/30, 77%) followed by beef (25/40, 63%), mutton (15/30, 50%), knives (18/40, 45%), nasal swabs (7/20, 35%), working area (11/40, 28%), rectal swabs (5/20, 25%), hooks (7/40, 18%) and butcher hands (7/40, 18%). 50 MRSA-positive isolates were chosen to identify two virulence factors (spa and coa gene). Of the 50 MRSA isolates subject to coa and spa gene typing, 27 (54%) were positive for the coa gene and 18 (36%) were positive for the spa gene, respectively. To the best of our knowledge, this was the first study on the molecular identification of MRSA in meat samples from Pakistan. High prevalence of MRSA in meat samples demand for implementation of proper hygienic practices and procedures during the slaughtering, transport and marketing of meat and meat products in order to prevent the spread of these bacteria to the human population.